Analysis Of Attitudes And Consumer Interest In Buying Organic Vegetable In The Modern Market Of Medan - Yudha Andriansyah Putra (JASc (Journal of Agribusiness Sciences), 2018)
More and more attributes of consumer preference in meeting the needs of vegetables, resulting in the involvement of consumers in selecting products vegetables are increasingly taken into account. the retail entrepreneur should seek constantly to meet the satisfaction of consumers in order to arise consumer loyalty. This research aims to analyze the sejauhmana relationship satisfaction with loyalty of consumers in buying organic vegetables, and how differences of attitude and consumer interest in buying organic vegetable in Carrefour plaza Medan fair, and Supermarket Brastagi, Medan. The data used in this research is the primary data (directly from consumers who buy organic vegetable) and secondary data (Data from  institutions that support this research). Methods of analysis used Multiple Linear Regression is by using the software SPSS 17.The results of the analysis show that with the above comparison is obtained, then significantly = 0 means there is no relationship between consumer satisfaction in purchasing with consumer loyalty research at both locations. The second means that shopping has the distinction of the average consumer's attitudes towards attributes Carrefour, in Plaza Medan Fair with Supermarket Brastagi Medan. On both of these shopping areas are statistically Independent test-with Sample T Test there is a difference in the average consumer's attitudes towards attributes in buying fruits in Carrefour, Plaza Medan Fair with Supermarket Brastagi Medan. There is no difference in the average consumer to buy interest in Carrefour, Plaza Medan Fair with Supermarket Medan Brastagi on 1 week, 2 weeks, 1 month and